2015
DOI: 10.1016/j.petrol.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surfactants on the deformation and break-up of an aqueous drop in oils under high electric field strengths

Abstract: Abstract:Understanding the deformation and break-up of drops is of great significance in various applications such as emulsification and phase separation. Most practical systems contain surface-active agents that are present as impurities affecting the properties of the system, e.g. modifying the rigidity of the film that affects emulsion stability. In this paper, the effect of surfactants on the deformation and break-up of an aqueous drop in an immiscible dielectric oil under the action of an electric field i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The effect of surfactants on the electro-deformation of neutrally buoyant drops was investigated by experimental techniques (Ha & Yang, 1998) and the corresponding theoretical models were also presented (Ha & Yang, 1995;Teigen & Munkejord, 2010;Nganguia et al, 2013). Zhang et al (2015) studied the role of nonionic surfactant on the deformation and breakup characteristic of a water droplet in a surrounding oil medium. Later, Ervik et al (2018) showed how the insoluble surface active agents can affect the oscillating nature of droplets under AC electric field.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of surfactants on the electro-deformation of neutrally buoyant drops was investigated by experimental techniques (Ha & Yang, 1998) and the corresponding theoretical models were also presented (Ha & Yang, 1995;Teigen & Munkejord, 2010;Nganguia et al, 2013). Zhang et al (2015) studied the role of nonionic surfactant on the deformation and breakup characteristic of a water droplet in a surrounding oil medium. Later, Ervik et al (2018) showed how the insoluble surface active agents can affect the oscillating nature of droplets under AC electric field.…”
Section: Introductionmentioning
confidence: 99%
“…However, when surfactants are added to this picture, the literature is not so extensive. Previous authors (Ha and Yang, 1998;Zhang et al, 2015) have investigated the influence of surfactants on the electrohydrodynamic stretching experimentally, but they have been limited to considerations of the static (equilibrium) deformation, as well as drop sizes above 1 mm in diameter, and a limited number of observations. Computational studies in the literature, namely previous work by , and the paper by Nganguia et al (2013) which finds good agreement with , have also been focused on the static deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed that an increase in the frequency of the PEF suppressed the formation of secondary droplets in the low-frequency electric domain. Zhang et al [139] examined the influence of a demulsifier on the distortion and breakup of hydrous drops in an immiscible dielectric oil under the effect of an electric source. The experimental runs were performed in a single drop microscopic cell under an external electric field.…”
Section: Electrical Demulsificationmentioning
confidence: 99%